Potensi Pembelajaran Yang Berorientasi ESD (Education For Sustainable Development) Pada Guru IPA Kelas 7 MTS Kabupaten Banjarnegara - Mulyani, Tri; Dewi, Endah Rita Sulistya; Hayat, Muhammad Syaipul (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
This study aims to describe the potential for ESD (Education for Suistanable Development)-oriented learning in grade 7 science teachers at MTs Banjarnegara District. The research method uses descriptive qualitative. The population in this study were 20 class VII teachers at MTs in Banjarnegara Regency. The instrument used in this study was a questionnaire distributed online to MTs science teachers based on ESD-oriented Teacher Potential indicators to obtain data and interview techniques. From the survey results, it was obtained information on teachers' knowledge about ESD, 65% did not know ESD, 70% did not know concepts and ESD in science learning. From other facts from the interviews it turned out that teachers did not know ESD in learning. From the results of the learning potential questionnaire, teachers' insights about ESD obtained 35% new to Education For Sustainable Development (ESD), 55% did not know the meaning of ESD and 60% had just heard of ESD. Some teachers in learning already know and find ESD-oriented material.